Necessity of Intensive Care Requirement in Childhood Intoxicity - Ebru Atike Ongun; Cemile Ece Çağlar Şimşek (Galenos Yayinevi, 2020)
Introduction:The aim of this study is to analyze the interventions of acute intoxications in pediatric intensive care unit (PICU) admissions and to determine the aspect of critical care support by using the demographic and clinical outcomes.Methods:593 PICU admissions due to intoxications between 2013 and 2018 were enrolled in the study. Demographics, drugs/substances received, voluntary or accidental drug intake, time of elapse from drug intake to PICU admission, length of PICU stay and hospitalization, adverse effects (clinically significant and non-clinically significant effects), PICU interventions, PRISM-3 score and clinical findings were extracted from the files.Results:Accidental poisonings mainly occurred in 2-5-year-old children, in males (51.2%) at summer season. Antipiretics/analgesics, cardiac medications and insecticides were the most frequent substances. Children with voluntary poisonings had increased multi-drug intake, higher PRİSM-3 scores, longer PICU stay and hospitalization (p<0.001, p=0.046, p=0.001, p<0.001). Thirty-six (6.1%) children presented 82 adverse effects mainly involving cardiovasculary and neurological systems. Tachycardia was frequent with no observed dysrhythmia. Adrenalin infusions were administered to two children for intractable hypotension; another two patients received atropin iv. bolus for bradycardia respectively. One adolescent received mechanical ventilation due to incapability to sustain airway maneuver. None required hemodialysis. The time of elapse from drug intake to PICU admission was 6.21±2.86 hours with total length of PICU stay of 1.38±0.76 days and hospitalization of 3.45±1.49 days.Conclusion:Future studies should focus on the prediction of intensive care requirement by the evaluation of the initial clinical signs in childhood intoxicity. Declining unnecessary PICU admission would facilitate the utilization of intensive care beds for the critically ill children and the minimalization of health care costs.